Medication through Temple Flora - V. Rose Geetha, Dr.S.Rajaram (International Journal of Advanced Science and Technology, 2020)
Plants are the basic source of livelihood for all beings in the world. Plant kingdom is broadly classified based on the utility as Food crops, Cash crops and Herbs or Medicinal Plants. Since early days, people have associated medicinal plants and trees with gods and temples since they are life saviours. Every temple has a temple tree, revered and worshipped with the deity or, otherwise, near the sacred tree, deities were established and people started worshipping them, protecting the trees near them with divinity. This article describes how the temple trees( generally called as sacred groves, when seen in large numbers) are used as lifesaving medicines and relief for ailing people.